Application of small extracellular vesicles in the diagnosis and prognosis of nasopharyngeal carcinoma - Zhang, Jiali; Huang, Defa; Lan, Xianbin; Deng, Dongming; Li, Jijing; Zhang, Dongzhi; Li, Yue; Zhong, Tianyu; Peng, Shaoping (Frontiers in Cell and Developmental Biology, 2023)
Nasopharyngeal carcinoma (NPC) is a malignant tumor originating from the epithelium of the nasopharynx. The disease is insidious, and most patients are diagnosed at the advanced stage, resulting in poor prognosis. Early diagnosis is important to reduce NPC mortality. Small extracellular vesicles (sEVs) are rich in a variety of bioactive molecules, such as proteins, nucleic acids, and lipids, which can participate in the physiological and pathological regulation of the body by affecting the function of target cells. Numerous studies have shown that some RNAs and proteins in sEVs of tumor origin have a key role in the development of NPC and are potential candidates for malignancy detection. Studying the relationship between the cargoes of these sEVs and NPC may help in the diagnosis of the disease. Here in this review, we summarize the application of sEVs as biomarkers in the diagnosis of NPC and their role in NPC metastasis and prognosis. In addition, we discuss possible future applications and limitations of sEVs as biomarkers.